Pengaturan Debit Air Berdasarkan Volume Air Dalam Tangki Berbasis Imperalis Competitive Algorithm (ICA) - Markhaban Siswanto; Mohammad Hasib Al Isbilly; Asnun Parwanti; Machrus Ali (FT- UNDAR, 2017)
An aquatic industry needs a good fluid flow measurement control system. Determination of the quantity of water is reduced because the volume of water in the holding tank varies. The effort to overcome this problem is made a system of performance regulation of water flow based on the volume of tanks with PID controls based on Imperalis Competitive Algorithm (ICA). This system uses ICA as a PID controller controller on a mini computer, flow sensor as a water speed detector, electric ball valve as an actuator. The working principle of this tool is to stabilize the output water speed per minute at a predetermined set point. This study compares 3 models; without control, PID control, PID Ziegler Nichols control, and PID controlled ICA controls. The simulation results in the study showed that the best control design in the study was the PID-ICA with the smallest overshot water level of 0.0154 pu, the smallest undershot water level of 0.0134 pu, the smallest overshot flow of 0.0102 pu, and the smallest undershot of 0.0097 pu.